Using newsgroup headers to predict document relevance - Christopher Brown-Syed; William Morrissey (Information Research: An International Electronic Journal)
Describes a pilot study of Usenet Newsgroup postings about Philosophy. The aim of the research is to arrive at a set of predictors of the quantity and usefulness of documents posted on the Net with the aim of assisting educators in the development of curricula, and LIS practitioners in the assessment of networked resources. In particular, we wished to see whether relationships existed between the layout of digital artefacts and the usefulness and reliability of their content.